2020
DOI: 10.1126/sciadv.aaz1469
|View full text |Cite
|
Sign up to set email alerts
|

The vertebrate-specific VENTX/NANOG gene empowers neural crest with ectomesenchyme potential

Abstract: During Cambrian, unipotent progenitors located at the neural (plate) border (NB) of an Olfactoria chordate embryo acquired the competence to form ectomesenchyme, pigment cells and neurons, initiating the rise of the multipotent neural crest cells (NC) specific to vertebrates. Surprisingly, the known vertebrate NB/NC transcriptional circuitry is a constrained feature also found in invertebrates. Therefore, evidence for vertebrate-specific innovations endowing vertebrate NC with multipotency is still missing. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 43 publications
6
69
4
Order By: Relevance
“…However, this model is debated since single-cell transcriptomes have shown that the multipotency gene signature proposed by Buitrago-Delgado et al was not specific to multipotent cells (Briggs et al, 2018). Rather, functional analysis of the vertebrate-specific genetic innovations Nanog/Oct4 (and their orthologs Ventx/ Pou5) before or after gastrulation rather suggests that NC progenitors de novo activate pluripotency regulators after NB induction (Scerbo and Monsoro-Burq, 2020). This reinitiates multipotency and promotes the ectomesenchyme fate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this model is debated since single-cell transcriptomes have shown that the multipotency gene signature proposed by Buitrago-Delgado et al was not specific to multipotent cells (Briggs et al, 2018). Rather, functional analysis of the vertebrate-specific genetic innovations Nanog/Oct4 (and their orthologs Ventx/ Pou5) before or after gastrulation rather suggests that NC progenitors de novo activate pluripotency regulators after NB induction (Scerbo and Monsoro-Burq, 2020). This reinitiates multipotency and promotes the ectomesenchyme fate.…”
Section: Discussionmentioning
confidence: 99%
“…This reinitiates multipotency and promotes the ectomesenchyme fate. From an evolutionary perspective, the cranial NB/NC-GRN requires Ventx/Nanog, Pou5/Oct4 and later NC specifier Ets1 to promote jawed structures formation in gnathostomes (Simoes-Costa and Bronner, 2016;Martik et al, 2019;Soldatov et al, 2019;Scerbo and Monsoro-Burq, 2020). Later on, NC specifiers' downregulation leads to the loss of pluripotency and the initiation of cell differentiation (Dottori et al, 2001;Sasai et al, 2001;Teng et al, 2008;Betancur et al, 2010;Mundell and Labosky, 2011;Dupin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ventx2 is broadly expressed in the neural plate border. 170 Knockdown of Ventx2 selectively affected expression of the NC specifiers Snail2, Sox9, Sox10, and Twist1 whereas Myc, Tfap2a, and Foxd3 levels were unaffected. 170 This altered expression profile resulted in reduced migration to the pharyngeal arches and reduced craniofacial skeleton whereas the neuronal lineage was unaffected in vivo and in vitro (in comparison, the melanocytic lineage was affected in vitro but not in vivo).…”
Section: Nanog (Maintenance Of Stemness)mentioning
confidence: 96%
“…170 This altered expression profile resulted in reduced migration to the pharyngeal arches and reduced craniofacial skeleton whereas the neuronal lineage was unaffected in vivo and in vitro (in comparison, the melanocytic lineage was affected in vitro but not in vivo). 170 Furthermore, ectopic NC cells that were not biased toward any certain fate were formed in the ectoderm lateral to the NC domain in a process that required Ventx2, thus suggesting a role for Ventx2 in enabling the NC with a broader potential than just being restricted to neural derivatives, which would be the default for an ectodermal cell population. 170…”
Section: Nanog (Maintenance Of Stemness)mentioning
confidence: 99%
See 1 more Smart Citation